Pertanggungjawaban Pidana Oleh Korporasi Dalam Tindakan Pelanggaran HAM di Indonesia - Yustitianingtyas, Levina (Faculty of Law, Universitas Ahmad Dahlan, 2016)
This law research focuses on the issue of how the corporate criminal liability for human rights violations in Indonesia is. The method used is normative juridical. This research concluded that first, the corporate criminal liability for human rights violations is necessary, not only because sometimes countries are not prepared and do not have power to convict the corporation by reason of fear to bear the negative economic consequences, but also because the corporation is proved able to commit human rights violations that cause remarkable and prolonged negative effects, second, the protection of human rights in Indonesia has not maximally implemented yet until now becauseÂ the recognition of the corporation as the subject offense in violations of human rights will have implications for the formulation of participation in criminal acts, limitation of liability, and other forms of criminal sanctions.